Evaluating Intra- and inter-rater reliability for "Cleft palate speech assessment test based on universal parameters system- in Persian" - Azadeh Amirian; Fatemeh Derakhshandeh; Ahmad Salehi; Bahram Soleimani (Vesnu Publications, 2012)
Introduction: Cleft palate is one of the most common congenital birth defects. Individuals with cleft palate have certain speech characteristics that can be identified perceptually by speech-language pathologists. Perceptual assessment has been regarded to as the gold standard for evaluating cleft palate speech. Considering the prevalence of cleft palate and its related speech characteristics, it is necessary for clinicians to use a reliable test for perceptual assessment of cleft palate speech errors. The aim of this study was to evaluate Intra- and inter-rater reliabilities for a recently developed assessment tool named "Cleft palate speech assessment test based on universal parameters system- Farsi version". Materials and Methods: In this descriptive-analytic cross-sectional study, speech samples obtained from 34 five-to-nine-year-old Farsi-speaking children with cleft palate who were referred to Isfahan cleft palate clinic were rated by two speech-language pathologists (one of them was considered as a naive and the other one as an expert rater). Two months later, 30% of the same speech samples were randomly selected and rerated by the same raters. Speech materials included 40 single words and 17 sentences along with a sample of connected speech. Intra- and inter-rater reliability measures were calculated via Intraclass Correlation Coefficient (ICC). Results: Mean Intra-rater reliability measured by ICC was found to be 0.967 and 0.971 for the naive and expert raters respectively. Mean Inter-rater reliability was 0.957 as measured by ICC. Conclusion: This test has an acceptable Intra and inter-rater reliability to be used in assessment of cleft palate speech and can be applied in those studies aimed at evaluating different aspects of speech in Farsi-speaking children with cleft palate aged from 5 to 9 years. Keywords: Cleft palate, Reliability, Perceptual speech assessment, Universal parameters system